Feminist Practices in Julie Shigekuni’s Invisible Gardens: A Japanese American Woman in the Twenty-First Century - Ina C Seethaler (Atlantis)
This article analyzes how Julie Shigekuni’s (2004) novel Invisible Gardens offers a Japanese American feminist perspective on women’s lives. The feminist themes explored include patriarchal familial relationships, the significance of mental spaces of refuge—like a garden and other ‘beyond’ spaces—and the explicit celebration of the (sexual) body as a site of women’s empowerment.